Design and fabrication of steering system for student formula race car - Arpin, Muhammad Afiq; Sharudin, Hazim (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The steering system plays an integral role in determining the car's handling, reactivity, and driver control. A common problem with formula racing cars is loose steering, which can be caused by wear and damage to the steering linkage components. This can have an impact on other parts attached to the linkage components, such as the steering wheel, and develop excessive play when rotating the wheels. Therefore, this study's aim is to produce an existing steering system that uses the best mechanism and is supported by a support that can hold it all the time through the use of high-quality materials, precision manufacturing techniques, and rigorous testing and validation processes. Elements like weight, strength, ergonomics and manufacturability must be considered in the design process. Examination of new ideas and technologies through extensive research improves the performance of the steering system. The primary objective of this project is to design and fabricate a complete steering system with its support system, which was accomplished after the project was completed. By means of rigorous design iterations and testing phases, it has met the goals with noteworthy success. In conclusion, this steering system prototype can be used in a single-seated race car to improve vehicle handling and turning.